الشيخ محمد الطيب بن الحواس هرباجي (1873-1931) - بن ساعو محمد (University Of Eloued جامعة الوادي, 2023)
الشيخ محمد الطيب هرباجي (1873-1931) هو نموذج عن المشيخات الريفية في منطقة جنوب سطيف التي تجمع بين تملك الأراضي وتمثيل الزاوية، فكان هذا الحضور المزدوج خلال الفترة الاستعمارية مهما لاعتبارات عديدة. سواء بالنسبة للأهالي أو لقواعد الحركة الوطنية التي باشرت مسار الهيكلة، وحتى بالنسبة للسلطات الاستعمارية. خلصنا من خلال هذه الدراسة البيوغرافية إلى أن هذا النوع من الأعلام المحليين كان لهم دور بارز في الحياة الثقافية والسياسية في الجزائر خلال الفترة الكولونيالية، خاصة وأن الاستعمار الفرنسي لم يغفل عن مكانتهم فحاول صياغة استراتيجية تحقق التوازن في إدارة القضايا المتعلقة بهم، خاصة وأنهم يتمتعون بنوع من الحظوة لدى الأهالي. Sheikh Mohammed Tayeb Ben El-Hawas Harbadji (1873-1931) is a model of the rural sheikhdoms in the southern Setif region that combine land ownership and representation of the Zawiya. This dual representation during the colonial period was important for many considerations. Whether for the indigenous or for the bases of the national movement that embarked on the path of structuring, and even of the colonial authorities. We concluded through this biographical study that this type of local personalities had a prominent role in the cultural and political life in Algeria during the colonial period, especially since the French colonialists were aware of the nature of their status. He tried to formulate a strategy that achieves balance in managing issues related to them, especially since they enjoy the respect of many indigenous.
دراسة بيوغرافية
Keywords: محمد الطيب هرباجي; جنوب سطيف; الزاوية; الإصلاح; التعليم; Mohammed Tayeb Harbadji; southern Setif; Zawiya; reform; education